Role of hysteroscopy for diagnosis and treatment of uterine factors affecting subfertility - DH, Nayana; S., Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysteroscopy has become the gold standard for diagnosis of intrauterine abnormalities. Intrauterine lesions such as adhesions, uterine septum polyps or submucous myomas are diagnosed much more precisely by hysteroscopy and are detectable in 10-15% of women seeking treatment for subfertility. The present study analyses various etiological factors in infertility diagnosed by hysteroscopy and to evaluate therapeutic interventions done during hysteroscopy. Methods: The cases for the study will include all women with primary or secondary infertility admitted in tertiary health centre from April 2016 to May 2018 for hysteroscopy. Results: Out of 90 subjects 66 (73.3%) were primary infertility and 24 (26.7%) were secondary infertility. Out of 90 cases studied, 68 (75.6%) had normal findings, 10 (11.1%) had endometrial polyps, 01 (1.1%) had submucous fibroid, 5 (5.6%) had septate uterus, hyperplastic endometrium in 3 (3.3%) and atropic endometrium in 1 (1.1%), intrauterine adhesions and hypoplastic uterus in 1 each. Hysteroscopic interventions were performed in the form of curettage in 08 (33.3%), hysteroscopic cannulation in 2 (8.3%), polypectomy and septal resection in 5 (20.8%) cases each, submucosal fibroid resection in 1 (4.2%) cases, tubal block released in 2 (8.3%). Conclusions: Hysteroscopy was found the best method in evaluation of intrauterine conditions for subfertility and also the type and location of uterine abnormalities can be precisely noted. The removal of those changes during operative hysteroscopy increases the fertility rate in women treated during this procedure.